Patients' and Physiotherapists' Views on Triggers for Low Back Pain. Issue 4 (February 2016) - Stevens, Matthew L.; Steffens, Daniel; Ferreira, Manuela L.; Latimer, Jane; Li, Qiang; Blyth, Fiona; Maher, Chris G.
Abstract : Supplemental Digital Content is available in the text Abstract : Study Design: A cross-sectional survey. Objective: The aim of this study was to compare patients' and physiotherapists' views on triggers for low back pain (LBP) and to identify any novel factors not previously reported. Summary of Background Data: Most research on risk factors for LBP is guided by the views of clinicians and researchers, not patients. Consequently, potentially valuable information about risk factors for LBP is not available from those suffering the condition. This study aimed to compare patients' and physiotherapists' views on triggers for LBP and to identify any novel factors not previously reported. Methods: One hundred two physiotherapists and 999 patients with a sudden, acute episode of LBP participated in this study. Participating physiotherapists were asked to nominate the most likely short-term risk factors to trigger a LBP episode. Similarly, patients were asked what they thought had triggered their onset of LBP. Responses were coded into risk factor categories and subcategories by 2 independent researchers. Endorsement of each category was compared using the Pearson Chi-square statistic. Results: Both patients and physiotherapists endorsed biomechanical risk factors as the most important risk factor category (87.7% and 89.4%, respectively) and had similar levels of endorsement for 3 of the top 5 subcategories (lifting, bending, and prolonged sitting). There were significant differences in endorsement of awkward postures (13.4% vs 1.2%; P  < 0.001) sports injuries (15.9% vs 4.7%; P  < 0.001), physical trauma (3.4% vs 9.2%; P  < 0.001), and unaccustomed activity (2.3% vs 7.3%; P  < 0.001) by patients and physiotherapists, respectively. Conclusion: Overall, patients' and physiotherapists' views were remarkably similar. Both patients and physiotherapists endorsed lifting as the most important trigger for LBP and agreed on 3 of the top 5 (lifting, bending, and prolonged sitting). No new risk factors were suggested by patients. Level of Evidence: 2